Adherence to activity monitoring devices or smartphone applications for improving physical activity in adults with cardiovascular disease: a systematic review protocol. (August 2018) - Kourbelis, Constance; Franzon, Julie; Foote, Jonathon W.; Brown, Alex; Daniel, Mark; Coffee, Neil T.; Newman, Peter; Ganesan, Anand; Nicholls, Stephen; Clark, Robyn A.
ABSTRACT: Review question: The question of this review is: what is the adherence to the use of activity monitoring devices or applications to improve physical activity in adults with cardiovascular disease? Specifically, the review objectives are: To quantify the extent of adherence (as specified by the study protocol) in the use of activity monitoring devices in the last five years. To determine if the extent of adherence differs by gender, age, length of study, types of device and/or how the device is worn. To determine if wearing an activity tracking device changes participants' level of physical activity. To determine the perceived acceptability (satisfaction) of participants using an activity monitoring device or application to change levels of physical activity.